Protein phosphatase 2A inactivation induces microsatellite instability, neoantigen production and immune response - Yen, Yu-Ting; Chien, May; Wu, Pei-Yi; Ho, Chi-Chang; Ho, Chun-Te; Huang, Kevin Chih-Yang; Chiang, Shu-Fen; Chao, K. S. Clifford; Chen, William Tzu-Liang; Hung, Shih-Chieh (Nature communications, 2021)
Microsatellite-instable (MSI), a predictive biomarker for immune checkpoint blockade (ICB) response, is caused by mismatch repair deficiency (MMRd) that occurs through genetic or epigenetic silencing of MMR genes. Here, we report a mechanism of MMRd and demonstrate that protein phosphatase 2A (PP2A) deletion or inactivation converts cold microsatellite-stable (MSS) into MSI tumours through two orthogonal pathways: (i) by increasing retinoblastoma protein phosphorylation that leads to E2F and DNMT3A/3B expression with subsequent DNA methylation, and (ii) by increasing histone deacetylase (HDAC)2 phosphorylation that subsequently decreases H3K9ac levels and histone acetylation, which induces epigenetic silencing of MLH1. In mouse models of MSS and MSI colorectal cancers, triple-negative breast cancer and pancreatic cancer, PP2A inhibition triggers neoantigen production, cytotoxic T cell infiltration and ICB sensitization. Human cancer cell lines and tissue array effectively confirm these signaling pathways. These data indicate the dual involvement of PP2A inactivation in silencing MLH1 and inducing MSI. Microsatellite instability (MSI), caused by deficiency of the DNA mismatch repair system, has been associated with improved response to immune checkpoint blockade (ICB). Here the authors show that inactivation of protein phosphatase 2A induces a MSI status, promoting cytotoxic T cell infiltration and response to ICB in pre-clinical cancer models.